Can environmental information disclosure attract FDI? Evidence from PITI project. (1st June 2023) - Pan, An; Qin, Yaoyao; Li, Han; Zhang, Wenna; Shi, Xunpeng
Abstract: Based on the balanced panel data of 260 prefecture-level cities in China from 2005 to 2016, and the quasi-natural experiment of the Pollution Information Transparency Index (PITI) project implemented in 110 prefecture-level cities in 2009, this paper uses the spatial difference-in-differences (SDID) model and the spatial Dubin model (SDM) model to investigate the FDI attraction effect of environmental information disclosure (EID). The results show that EID will significantly promote the inflow of FDI in cities, and this effect will be stronger with the increasing disclosure extent. EID has a siphon effect on FDI, that is, a city that has a better EID will attract more FDI than its neighbors, further intensifying the competition effect of FDI among cities with similar geographical distance, levels of economic development, and Internet penetration. The attraction effect of EID on FDI is mainly present in polluting cities and non-resource-based cities, while the impact on clean and resource-based cities is not significant. Highlights: We analyze the attraction effect of environmental information disclosure on FDI. The effect of PITI project is evaluated with spatial-DID and SDM methods. Environmental information disclosure has a siphon effect on FDI among cities. The FDI attraction effect of disclosure extent is heterogeneous in city characters.